Cases of Violation of the Principle of Equal Treatment in the Field of Employment Relationships of Public Property Inspectors and Assistant Inspectors - Békési, László (Magyar Rendészet, 2015)
The main objective of Act CXXV of 2004 on equal treatment and the promotion of equal opportunities is to promote the conformity with the principle of equal treatment, including — inter alia — the legal relationships of local governments. In terms of performing the policing duties of local governments, more specifically concerning the jobs of public property inspector and assistant inspector, respectively, significant differences can be observed in the rules pertaining to the same types of employment of the laws governing said jobs (Mt. and Kttv.). This study is aimed at disclosing said discrepancies and proposing solutions to their elimination in conformity with the respective EU directives.